2018
DOI: 10.1371/journal.pone.0190033
|View full text |Cite
|
Sign up to set email alerts
|

Association of loneliness with all-cause mortality: A meta-analysis

Abstract: IntroductionLoneliness has social and health implications. The aim of this article is to evaluate the association of loneliness with all-cause mortality.MethodsPubmed, PsycINFO, CINAHL and Scopus databases were searched through June 2016 for published articles that measured loneliness and mortality. The main characteristics and the effect size values of each article were extracted. Moreover, an evaluation of the quality of the articles included was also carried out. A meta-analysis was performed firstly with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
297
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 401 publications
(325 citation statements)
references
References 80 publications
13
297
0
15
Order By: Relevance
“…There is increasing recognition of the link between loneliness and negative health outcomes. Results from two metaanalyses suggest that loneliness is a predictor of all-cause mortality, with a 22%-26% increased risk of death found in those reporting high levels of loneliness (Holt-Lunstad, Smith, Baker, Harris, & Stephenson, 2015;Rico-Uribe et al, 2018). Loneliness has also been linked with the onset of coronary heart disease (CHD) (Valtorta, Kanaan, Gilbody, Ronzi, & Hanratty, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing recognition of the link between loneliness and negative health outcomes. Results from two metaanalyses suggest that loneliness is a predictor of all-cause mortality, with a 22%-26% increased risk of death found in those reporting high levels of loneliness (Holt-Lunstad, Smith, Baker, Harris, & Stephenson, 2015;Rico-Uribe et al, 2018). Loneliness has also been linked with the onset of coronary heart disease (CHD) (Valtorta, Kanaan, Gilbody, Ronzi, & Hanratty, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…9 One of the measures of the perceived quality of social relationships is loneliness, 2 the sense of distress derived from perceived deficiencies in the social relationships one desires to have. 11 One's living arrangement, consisting primarily of social relationships of family members who share a set of cultural norms and values, represents a pivotal household context that promotes and/or restricts relationships, including their quantity and function. 11 One's living arrangement, consisting primarily of social relationships of family members who share a set of cultural norms and values, represents a pivotal household context that promotes and/or restricts relationships, including their quantity and function.…”
Section: Introductionmentioning
confidence: 99%
“…10 Loneliness has been reported by a number of studies as a significant risk factor for mortality. 11 One's living arrangement, consisting primarily of social relationships of family members who share a set of cultural norms and values, represents a pivotal household context that promotes and/or restricts relationships, including their quantity and function. 12 Although some research findings show that older adults' living alone is associated with a higher mortality rate, 13 some report otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Social contact has been connected to the release of oxytocin (Holt-Lunstad et al 2008). Loneliness has been associated with all-cause mortality in a previous meta-analysis study (Rico-Uribe et al, 2018). Specifically, it was found that individuals who have an anxious attachment style have an increased neurological sensitivity to social distress.…”
Section: Discussionmentioning
confidence: 98%